DEVELOPMENT OF PRODUCTION WAKAF FOR POVERTY REDUCTION IN CIAMIS DISTRICT - Pepe Iswanto; Saepulloh Saepulloh; Ana Husna Azizah (Syari'ah Economics, 2020)
This study aims to analyze the development of productive waqf to reduce poverty levels in Ciamis Regency. The research method used is empirical research. Data were collected through interviews and documentation studies. The results showed that (1) the management carried out by Nazhir used the POAC method (Planning, Organizing, Acting, Controlling) in order to achieve what was expected by the wakif so that the waqf property was utilized in accordance with its purpose; (2) implementation of waqf development through the establishment of mini markets. Until now, it has started to develop with the opening of a canteen near the area of educational institutions, laundry, and already has an inventory of two-wheeled vehicles. To increase productivity, a poverty alleviation model is currently being developed through scholarships for underprivileged and orphaned students. The obstacles faced in optimizing the program are limited capital, low competence of human resources